The application of expanded polystyrene cushion layer in oblique flexible net systems for rockfall protection: A new attempt. Issue 2 (June 2018) - Wang, Wenkang; Shi, Shaoqing; Liu, Yingfeng; Wang, Gaosheng
An expanded polystyrene cushion layer is usually not applied in flexible net systems for rockfall protection. This study presents a new attempt by conducting serial free-fall tests of blocks impacting oblique flexible net systems with and without expanded polystyrene cushion layers. Thus, axial forces of support ropes and the video of impact process were obtained. Additionally, finite element method numerical simulations were carried out based on ANSYS/LS-DYNA. The "self-cleaning" effect of oblique flexible net systems was depicted in detail. Furthermore, the attenuation effect of expanded polystyrene cushion layers was illustrated due to a decrease in axial forces, which can correspond to a maximum of 22.1%. A comparison of axial forces between tests and finite element method numerical simulations was made, and this validated the efficiency of the finite element method numerical simulations.